IMPROVING ACTIVITIES AND STUDENT LEARNING RESULTS THROUGH THE APPLICATION OF THE PROBLEM BASED LEARNING MODEL IN PHYSICS LEARNING IN CLASS XI MIPA1 SMA NEGERI 12 PEKANBARU - Desta Velly (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
The results of the students' test of class XI MIPA1 SMA Negeri 12 Pekanbaru on the material of physics, shows that almost more than half of students have not been able to solve the problems well, it needs improvement or. Problem Based Learning is one of the recommended learning models in the implementation of the curriculum 2013 because this model is proven capable of stimulating high-level thinking ability with problem design in real context. The purpose of this action research is to improve learning outcomes and student activities in the application of Problem Based Learning model in Physics learning. The subject of this research is the students of class XI MIPA 1, SMA Negeri 12 Pekanbaru. This research is a classroom action research conducted in 2 cycles. The results of this study obtained data from the test results learners cycle I with absorption of 59.0%, the cycle II absorption of 69.3%, student activity on learning cycle I and cycle II active categories. Therefore, the implementation of Problem Based Learning can improvement the activity and learning outcome of physics learning for students of class XI MIPA1, SMA Negeri 12 Pekanbaru.